2014
DOI: 10.1007/s12032-014-0259-2
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant miR-215 expression is associated with clinical outcome in breast cancer patients

Abstract: Dysregulation of microRNA plays critical roles in various malignancies. However, whether the aberrant expression of miR-215 in breast cancer is associated with malignancy, metastasis, or prognosis remains unknown. In this study, we demonstrated that the relative level of miR-215 expression was lower in cancer tissues compared with adjacent non-malignant tissues (p < 0.001). Low-miR-215 expression was observed to be closely correlated with higher tumor grade (p = 0.008), human epidermal growth factor receptor 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 25 publications
1
31
1
Order By: Relevance
“…The expression level of miR-215 was demonstrated to be associated with the International Federation of Gynecology and Obstetrics stage, the histological grade, and the extents of vascular invasion and lymph node metastasis of cervical cancer; the 5-year survival rate was lower in patients with stage II cervical cancer who exhibited miR-215 overexpression (29). However, previous studies have also demonstrated that miR-215 may be downregulated in epithelial ovarian (30), pancreatic (31), non-small cell lung (32), breast (33) and colon (34) cancer. In the study on pancreatic cancer, a low expression level of miR-215 was significantly associated with a large tumor size, an advanced TNM stage, a high extent of lymph node metastasis and vessel invasion, and lower overall survival time; multivariate regression analysis demonstrated that miR-215 underexpression was an independent unfavorable prognostic factor for patients (31).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The expression level of miR-215 was demonstrated to be associated with the International Federation of Gynecology and Obstetrics stage, the histological grade, and the extents of vascular invasion and lymph node metastasis of cervical cancer; the 5-year survival rate was lower in patients with stage II cervical cancer who exhibited miR-215 overexpression (29). However, previous studies have also demonstrated that miR-215 may be downregulated in epithelial ovarian (30), pancreatic (31), non-small cell lung (32), breast (33) and colon (34) cancer. In the study on pancreatic cancer, a low expression level of miR-215 was significantly associated with a large tumor size, an advanced TNM stage, a high extent of lymph node metastasis and vessel invasion, and lower overall survival time; multivariate regression analysis demonstrated that miR-215 underexpression was an independent unfavorable prognostic factor for patients (31).…”
Section: Discussionmentioning
confidence: 98%
“…In the study on pancreatic cancer, a low expression level of miR-215 was significantly associated with a large tumor size, an advanced TNM stage, a high extent of lymph node metastasis and vessel invasion, and lower overall survival time; multivariate regression analysis demonstrated that miR-215 underexpression was an independent unfavorable prognostic factor for patients (31). miR-215 expression was also reported to be associated with a higher tumor grade, human epidermal growth factor receptor 2 (HER2)-positivity, HER2-positive breast cancer subtype and lymph node metastasis in breast cancer (33). These studies have indicated that miR-215 may be a diagnostic and prognostic biomarker for a number of types of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-215 was also identified as a putative anti-oncogenic miRNA through modulating a number of genes: up-regulated miR-215 causes a decrease in clonogenicity and mediates the repression of cell cycle and stemness genes downstream of CDX1 by targeting BMI1 in colon cancer (18,38), decreased cell migration and invasion in renal cell carcinoma (RCC) by targeting SIP1/ZEB2 and MMP3 (39); increased apoptosis by targeting XIAP in non-small cell lung cancer (40). However, up-regulation of miR-215 can also be observed in several studies such as gastric cancer, cervical cancer and hepatocellular carcinoma (41)(42)(43) (17). Prognostic significance of miR-215 expression has been revealed in many solid tumors, which suggests that it could serve as a potential role of prognostic biomarker and thereby create a more predictable future when refers to the clinical treatment of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that miR-215 could act as a tumor suppressor gene, and down-regulation of miR-215 was identified in several cancers, such as myeloma (14), nephroblastoma (15), esophageal adenocarcinoma (16), breast cancer (BC) (17) and colon cancer (18,19). However, the status of miR-215 expression and its prognostic value remain unclear in AML.…”
Section: Introductionmentioning
confidence: 99%
“…miR-874 has been shown to inhibit cell proliferation and induce apoptosis by targeting CDK9 (13). miR-215 functions as a prognostic predictor for breast cancer with its high expression in cancer tissues and its association with other clinicopathological factors and the survival of patients (14). These data suggest an important role for miRNAs in the biology of BC.…”
Section: Introductionmentioning
confidence: 87%